Temperature identification of a heat source in conjugate heat transfer problems via an inverse analysis. Issue 10 (26th September 2019) - Mayeli, Peyman; Nikfar, Mehdi
Abstract : Purpose: The present study aims to perform inverse analysis of a conjugate heat transfer problem including conduction and forced convection via the quasi-Newton method. The inverse analysis is defined for a heat source that is surrounded by a solid medium which is exposed to a free stream in external flow. Design/methodology/approach: The objective of the inverse design problem is finding temperature distribution of the heat source as thermal boundary condition to establish a prescribed temperature along the interface of solid body and fluid. This problem is a simplified version of thermal-based ice protection systems in which the formation of ice is avoided by maintaining the interface of fluid and solid at a specified temperature. Findings: The effects of the different pertinent parameters such as Reynolds number, interface temperature and thermal conductivity ratio of fluid and solid mediums are analyzed. Originality/value: This paper fulfils the analysis to study how thermal based anti-icing system can be used with different heat source shapes.